Beyond Legal Structure – Division of Competence between Home and Host States in the Prudential Supervision of Significant Credit Institution Branches in the EU - Aho, Katri (fi=Turun yliopisto|en=University of Turku|, 2017)
Subsidiaries and branches are treated differently in EU banking regulation. The branch is mostly within the competence of the home state, whereas the subsidiary is within the competence of the host state. Therefore, a mere change of legal structure has significance to the countries involved. The home country control approach in the supervision of branches was developed in the 1980s, but the financial markets have evolved much since. Nowadays, credit institutions organise even significant activities through branches. This thesis concentrates on the justifications of such differentiation, particularly from a host country perspective. The differences between the legal structures from a financial stability perspective are analysed. The competence division in EU banking supervision, resolution and deposit insurance is introduced. The focus is on significant branches as well as the border between the EU Member States participating and not participating in the Banking Union is taken into consideration. Furthermore, it is examined whether the differentiation is compatible with the EU freedom of establishment – after all, there is extensive case law by the Court of Justice of the European Union (CJEU) particularly in the field of tax law where it has established that the freedom of establishment entails the right to choose the legal structure of secondary establishment. The main sources for the research include legal and economic literature, CJEU case law as well as materials provided by the EU institutions and agencies. This thesis suggests that ring-fencing or restrictions on credit institutions’ freedom of establishment is not the optimal solution to the imbalance. The balancing act should be done at the level of secondary legislation, and certain improvements can be achieved even through minor adjustments. This thesis offers two main policy suggestions that should be pursued simultaneously – further centralisation of competence to the EU level and the balancing of certain aspects of secondary legislation. Particularly, the host state should have the macro-prudential competence regarding truly significant branches.

Tytäryhtiöitä ja sivuliikkeitä kohdellaan eri tavoin EU:n pankkisääntelyssä. Sivuliike on pääosin kotivaltion toimivallassa, kun taas tytäryhtiö on isäntävaltion toimivallassa. Näin ollen pelkkä juridisen muodon muutos vaikuttaa merkittävästi valtioiden toimivaltasuhtei-siin. Periaate kotivaltion toimivallasta sivuliikkeisiin sai alkunsa 1980-luvulla, mutta rahoi-tusmarkkinat ovat kehittyneet merkittävästi sen jälkeen. Nykyään luottolaitokset järjestävät jopa merkittäviä toimintoja sivuliikkeiden muodossa. Tämä pro gradu -tutkielma keskittyy juridisten muotojen erottelun oikeutukseen erityisesti isäntävaltion näkökulmasta. Tutkielmassa analysoidaan juridisten muotojen eroja erityisesti rahoitusvakausnäkökulmasta. Lisäksi tutkielma esittelee toimivallanjakoa EU:n pankkival-vonnassa, kriisinratkaisussa ja talletussuojassa. Tutkimus keskittyy merkittäviin sivuliikkei-siin sekä rajaan EU:n pankkiunioniin kuuluvien ja kuulumattomien jäsenvaltioiden välillä. Lisäksi tutkimuksessa on keskitytty siihen, onko tämä erottelu EU:n sijoittautumisvapauden mukainen – Euroopan unionin tuomioistuin (EUTI) on ratkaisukäytännössään erityisesti vero-oikeuden alalta todennut, että sijoittautumisvapauteen kuuluu myös oikeus valita tois-sijaisen sijoittumisen juridinen muoto. Pääasiallisina lähteinä tutkimuksessa on käytetty juridista ja taloustieteellistä kirjallisuutta, EUTIn ratkaisukäytäntöä ja EU:n toimielinten ja virastojen antamia materiaaleja. Tutkielmassa todetaan, että sijoittautumisvapauden rajoittaminen ei ole sopivin tapa ratkais-ta epätasapainoa. Tasapainottaminen tulisi tehdä toissijaisen pankkisääntelyn tasolla, ja joitakin parannuksia voidaan saada aikaan jopa pienillä muutoksilla. Tutkielmassa annetaan kaksi pääasiallista toimenpidesuositusta, joita tulisi tavoitella samanaikaisesti – toimivallan vahvempi keskittäminen EU-tasolle ja eräiden aspektien tasapainottaminen pankkisäänte-lyssä. Todella merkittävien sivuliikkeiden osalta erityisesti makrovakaustoimivallan tulisi olla isäntävaltiossa.